2016
DOI: 10.4236/ojped.2016.61019
|View full text |Cite
|
Sign up to set email alerts
|

Newborn Umbilical Cord Care in Parakou in 2013: Practices and Risks

Abstract: Objective: The objective was to study umbilical care practices and risks in Parakou (North Benin). Patients and method: It was a cross-sectional and descriptive study carried out within a community from June 1 to August 31, 2013. It focused on all the infants born at the maternity of Parakou Health Center and their mothers. Results: Two hundred and ten newborns were included i.e. 101 boys and 109 girls. In 80.9% of cases, inappropriate substances had been applied to umbilical cord. Umbilical cord care quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…The traditional practices related to infant health care associated with poor standards of hygiene, increase the risk for umbilical cord infection and even the risk of neonatal tetanus. Agossou et al made those same observations regarding umbilical care for newborns in a community-based study conducted in Parakou in 2013 [14]. The same remark was made by Amorissani et al who showed that neonatal morbidity related to traditional care was dominated by umbilical infections in 65.20% of cases [10].…”
Section: Frequency Of Neonatal Infections and Lethalitymentioning
confidence: 65%
“…The traditional practices related to infant health care associated with poor standards of hygiene, increase the risk for umbilical cord infection and even the risk of neonatal tetanus. Agossou et al made those same observations regarding umbilical care for newborns in a community-based study conducted in Parakou in 2013 [14]. The same remark was made by Amorissani et al who showed that neonatal morbidity related to traditional care was dominated by umbilical infections in 65.20% of cases [10].…”
Section: Frequency Of Neonatal Infections and Lethalitymentioning
confidence: 65%
“…Another study done in one public hospital in Nairobi, Kenya, supported this finding where 52% of mothers washed their hands under running water and 48% used water in basins 40 . Comparably, in Parakou, Benin, 73% of mothers expressed that they washed their hands prior to cord care provision 50 . Further, with regards to the washing substance in the current study, majority of mothers (44%) used water and soap.…”
Section: Discussionmentioning
confidence: 95%
“…Elsewhere, methylated spirit was the main cord care method in Ghana 48 and in Nigeria 41, 46,49 ; while use of brick ash was reportedly highly used in Zambia 22 . Findings from another study carried out in Benin reported that inappropriate/harmful substances were applied by 81% of caregivers 50 . In Ethiopia and Nigeria, dry cord care was widely exercised 51,52 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elsewhere, methylated spirit was the main cord care method in Ghana 48 and in Nigeria 41, 46, 49 ; while use of brick ash was reportedly highly used in Zambia 22 . Findings from another study carried out in Benin reported that inappropriate/harmful substances were applied by 81% of caregivers 50 . In Ethiopia and Nigeria, dry cord care was widely exercised 51, 52 .…”
Section: Discussionmentioning
confidence: 99%